Genome‐Wide Association Study of Developing Leaves' Heat Tolerance during Vegetative Growth Stages in a Sorghum Association Panel. Issue 2 (1st July 2017) - Chen, Junping; Chopra, Ratan; Hayes, Chad; Morris, Geoffrey; Marla, Sandeep; Burke, John; Xin, Zhanguo; Burow, Gloria
Abstract : Heat stress reduces grain yield and quality worldwide. Enhancing heat tolerance of crops at all developmental stages is one of the essential strategies required for sustaining agricultural production especially as frequency of temperature extremes escalates in response to climate change. Although heat tolerance mechanisms have been studied extensively in model plant species, little is known about the genetic control underlying heat stress responses of crop plants at the vegetative stage under field conditions. To dissect the genetic basis of heat tolerance in sorghum [ Sorghum bicolor (L.) Moench], we performed a genome‐wide association study (GWAS) for traits responsive to heat stress at the vegetative stage in an association panel. Natural variation in leaf firing (LF) and leaf blotching (LB) were evaluated separately for 3 yr in experimental fields at three locations where sporadic heat waves occurred throughout the sorghum growing season. We identified nine single‐nucleotide polymorphisms (SNPs) that were significantly associated with LF and five SNPs that were associated with LB. Candidate genes near the SNPs were investigated and 14 were directly linked to biological pathways involved in plant stress responses including heat stress response. The findings of this study provide new knowledge on the genetic control of leaf traits responsive to heat stress in sorghum, which could aid in elucidating the genetic and molecular mechanisms of vegetative stage heat tolerance in crops. The results also provide candidate markers for molecular breeding of enhanced heat tolerance in cereal and bioenergy crops.